Bahan Pembentuk Beton Terhadap Kuat Tekan Beton K275 - Andara, Marsha Nabila; Maulani, Ari Indra; Arif, Arif; Firmansyah, Pahrul; Puspitasari , Riska; Herol, Herol (JURNAL TEKNIK SIPIL, 2024)
Concrete is the most widely used construction material throughout the world, functioning as a structural element in various types of buildings, infrastructure and civil engineering projects. The strength and durability of concrete is greatly influenced by the composition of the ingredients that form it. One type of concrete that is widely used is K275 concrete, which is known for its ability to withstand heavy loads and its resistance to various environmental conditions. This research uses an experimental method by making concrete samples from various variations of forming materials. Tests were carried out on the mechanical properties of the aggregate, determining the optimal composition of the concrete mix, as well as testing the compressive strength after curing for 28 days. It is hoped that the research results will provide a deeper understanding of the specific influence of forming materials on the compressive strength of K275 concrete, as well as provide a significant contribution to better and environmentally friendly construction practices